أثر استخدام الإدارة الالكترونية على تنافسية البنوك دراسة حالة – بنك القرض الشعبي الجزائري – وكالة سوق اهراس - شيماء مراس; مروة عباسي (My University, 2023)
The aim of the study revolves around finding out the impact of the use of electronic management on the competitiveness of banks, which has become the latter of the most important resources that must be possessed in economic institutions, especially banks. In this regard, we relied on a questionnaire addressed to customers of the Algerian People's Credit Bank - Souk Ahras Agency - It consists of two axes, an axis that studies electronic management through the dimensions of the latter represented in: Tangibility, reliability, responsiveness and safety, and another axis that studies the competitiveness of banks. The study concluded that electronic management affects the competitiveness of banks, by relying on the indicators of statistical analysis in testing the hypotheses of the study, and this helps to raise the competitiveness of banks. Based on the results, recommendations were made. ..................................... يتمحور هدف الدراسة حول معرفة أثر استخدام الإدارة الإلكترونية على تنافسية البنوك التي أصبحت هذه الأخيرة من أهم الموارد التي يجب حيازتها في المؤسسات الإقتصادية وخاصة البنوك . استعنا في ذلك على إستبيان موجه لزبائن بنك القرض الشعبي الجزائري ـ وكالة سوق أهراس ـ مشكل من محورين ، محور يدرس الإدارة الإلكترونية من خلال أبعاد هذه الأخيرة المتمثلة في : الملموسية، الإعتمادية ، الإستجابة والأمان ومحور آخر يدرس تنافسية البنوك . وقد توصلت الدراسة إلى أن الإدارة الإلكترونية تؤثر على تنافسية البنوك ، وذلك بالإعتماد على مؤشرا التحليل الإحصائي في إختبار فرضيات الدراسة وهذا يساعد على رفع القدرة التنافسية للبنوك . بناءا على النتائج تم تقديم توصيات . ...................................... L'objectif de l'étude s'articule autour de la recherche de l'impact de l'utilisation de la gestion électronique sur la compétitivité des banques, qui est devenue la dernière des ressources les plus importantes que doivent posséder les institutions économiques, notamment les banques. A cet égard, nous nous sommes appuyés sur un questionnaire adressé aux clients de la Banque de Crédit Populaire d'Algérie - Agence Souk Ahras - Il se compose de deux axes, un axe qui étudie la gestion électronique à travers les dimensions de cette dernière représentées dans : Tangibilité, fiabilité, réactivité et sécurité, et un autre axe qui étudie la compétitivité des banques. L'étude a conclu que la gestion électronique affecte la compétitivité des banques, en s'appuyant sur les indicateurs de l'analyse statistique pour tester les hypothèses de l'étude, et cela contribue à accroître la compétitivité des banques. Sur la base des résultats, des recommandations ont été faites.